Community-based intervention in mosquito control strategy: A systematic review - Yulfi, Hemma; Panggabean, Merina; Darlan, Dewi M.; Siregar, Irma SS.; Rozi, Muhammad F. (Narra Sains Indonesia, 2025)
As part of the World Health Organization’s One Health Initiative, vector-borne disease control requires multidisciplinary and community involvement. This review examined community-based mosquito control intervention methods, their efficacy, and limitations. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guideline, data were extracted from four medical databases: PubMed, Clinical Key, ProQuest, and ScienceDirect, covering the period from 2014 to 2023. The search used the keywords